Plant genetic resources conservation and use in China: Proceedings of a National Workshop on Conservation and Utilization of Plant Genetic Resources, 25-27 October 1999, Beijing, China - Weidong Gao; Ramanatha Rao, V.; Ming-De Zhou; International Plant Genetic Resources Institute; CAAS (2001)
English and Chinese in one publication